Petrogenesis of late Ordovician high Ba–Sr quartz diorite in the northern Qinling orogeny and its geological implications - Du, Biao; Zhao, Duanchang; Zhang, Yafeng; Zhang, Zhenkai; Wang, Xing; Li, Wujie; Wang, Zilong (Frontiers in Earth Science, 2025)
Late Ordovician to early Silurian medium-acidic magmatic rocks with high Ba–Sr characteristics are well-exposed in the northern Qinling orogeny and are ideal objects for discussing the regional evolution of magmatism and constraint tectonics. The zircon U–Pb geochronology of quartz diorite in the northern Qinling terrane was assessed by laser-ablation inductively coupled plasma mass spectrometry and yielded a weighted mean age of 444 ± 3 Ma for 206Pb/238U, which was interpreted as the intrusion time of monzodioritic magma. The quartz diorite showed high Ba (357–886 ppm) and Sr (198–382 ppm) contents, consistent with the features of high Ba–Sr magmatic rocks. The high Ba–Sr quartz diorite samples showed high SiO2 and MgO contents of 58.26%–63.49% and 2.45%–3.20%, respectively, and possessed large FeOt/MgO ratios ranging from 1.71 to 2.02. In addition, the high Ba–Sr quartz diorite analyses were characterized by light-rare-earth-element-enriched as well as high-field-strength-element- and high-rare-earth-element-depleted patterns with moderate negative Eu anomalies (δEu = 0.61–0.81) as well as low ratios of Sr/Y (5–13) and (La/Yb)N (5–7), indicative of arc-magmatic-related affinities. Based on the above findings along with moderate Ba/Th, Ba/La, and Th/Nd ratios from the geochemical results, we propose that the high Ba–Sr quartz diorite was formed by partial melting of the enriched mantle wedge metasomatized by subduction fluids and melt interactions associated with the northward subduction of the Shangdan ocean. Therefore, the extensive late Ordovician magmatic activities driven by the metasomatic mantle wedge facilitated the early Paleozoic crustal growth of the northern Qinling orogeny.